Counterterrorism Planning in the Shipping Industry Leveraging Competitive Intelligence - Anastasios-Nikolaos KANELLOPOULOS; Anthony IOANNIDIS (Bulletin of "Carol I" National Defense University)
This paper addresses the critical need to bolster Counterterrorism (CT) strategies in the Shipping industry, which is responsible for the vast majority of global goods transportation. The objective is to advocate for the integration of Competitive Intelligence (CI) into CT planning to address current security deficiencies. Key threats such as piracy in Somalia and the Gulf of Guinea, ship-borne terrorism, and attacks on ports are examined, highlighting the limitations of existing measures like the International Ship and Port Facility Security (ISPS) Code. The first chapter delves into primary threats, including hijacking, piracy, ship-borne terrorism, and port attacks, providing an in-depth analysis of their implications and necessary countermeasures. The second chapter explores current CT measures, focusing on the role of the International Maritime Organization (IMO) and the effectiveness of the ISPS Code, while identifying the reactive nature of existing strategies. The third chapter proposes a strategic CI framework, emphasizing comprehensive data collection, advanced analysis, threat identification, and proactive strategy development. Each component is detailed to illustrate how CI can transform CT planning, making it more anticipatory and effective. The authors anticipate that using CI will help stakeholders, including policymakers, Shipping companies, and security agencies, adopt more proactive and effective measures against emerging threats. The proposed framework emphasizes the importance of stakeholder collaboration, public-private partnerships, and international cooperation. This study aims to enhance maritime security, ensure global trade’s safe and efficient operation, and improve global maritime resilience, offering valuable insights for all industry stakeholders.